High Prevalence of Elevated Factor VIII Levels in Patients Referred for Thrombophilia Screening: Role of Increased Synthesis and Relationship to the Acute Phase Reaction - O’Donnell, J; Tuddenham, E G D; Manning, R; Kemball-Cook, G; Johnson, D; Laffan, M (Thrombosis and Haemostasis, 1997)
A recent report from the Leiden Thrombophilia Survey identified high factor VIII activity levels as an independent risk factor for venous thromboembolism in a population survey. As the study measure for factor VIII was a one-stage coagulation assay, and since markers for the acute phase reaction were not assessed, it remained uncertain whether the increase was due to a constitutional increased rate of synthesis, to circulating activated factor VIII, or to an acute phase response.We added factor VIII activity assay (FVIII:C), factor VIII antigen (FVIILAg), vWF antigen (vWF:Ag), ABO blood group, fibrinogen and C-reactive protein to our routine thrombophilia screen of patients referred because of unexplained thromboembolism.Elevated FVIILC (>1.5 iu/ml) emerged as the single commonest abnormality detected in 25.4% of a group of 260 such patients.FVIILC and FVIILAg were highly correlated (p = 0.003), showing that this represented a true increase in FVIII. In 4 of 46 patients this was clearly attributable to an acute phase reaction. Eleven others showed minor elevation of ESR and one of CRP. Neither FVIILC or FVIII:Ag showed significant correlation with fibrinogen, ESR or C-reactive protein by non parametric analysis.Although there was an excess of patients with B blood group (known to be associated with FVIILC levels which are -15% higher than those in blood group 0), this could not account for the marked elevation of factor VIII observed in these patients.We conclude that factor VIII activity assay should be a routine part of thrombophilia screening. We are investigating the cause of the increased synthesis, initially by means of family studies and linkage analysis with polymorphic markers of the FVIII locus. We postulate that it may be constitutive in some cases and in others an abnormal or exaggerated response to inflammatory stimuli.